1998
DOI: 10.1108/13639519810228732
|View full text |Cite
|
Sign up to set email alerts
|

Police academy fitness training at the Police Training Institute, University of Illinois

Abstract: The Police Training Institute at the University of Illinois designed a fitness training programme which allowed the participants to choose the intensity and mode of their exercise. Between June 1993 and March 1995, the incoming recruits’ fitness level was assessed before and after the training programme in order to measure the improvement induced by the training and to compare the recruits’ fitness level to the general population. The recruits significantly improved their flexibility (19.10 vs 15.13 degrees) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 12 publications
(13 reference statements)
3
14
0
1
Order By: Relevance
“…Both groups had gained an average of 2kg of grip strength; this is similar to the improvement previously observed in the recruits at the end of the academy (Copay and Charles, 1998). This improvement is most likely due to the daily physical training in which recruits participate and possibly to the classes involving manual skills such as that required in the firearms and control tactics curriculum.…”
Section: Grip Strength and Marksmanship Improvementsupporting
confidence: 74%
“…Both groups had gained an average of 2kg of grip strength; this is similar to the improvement previously observed in the recruits at the end of the academy (Copay and Charles, 1998). This improvement is most likely due to the daily physical training in which recruits participate and possibly to the classes involving manual skills such as that required in the firearms and control tactics curriculum.…”
Section: Grip Strength and Marksmanship Improvementsupporting
confidence: 74%
“…Nevertheless, there is no consensus in the literature when it comes to quantifying it. Some studies suggested great percentages [9], while others confered small percentages of influence [8,9]. Shooters also think that physical condition has an influence on psychological state and mental wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the general aspects related to fitness training (FT) could affect shooting performance by 12% [8]. According to the experts, the importance of FT in shooting performance oscillates between 3% and 46% [9]. Furthermore, the studies which determined muscular influence on shooting performance (maximum score obtained) presented greater discrepancies, with values of 67%–79% when shooters used a 0.22-inch calibre at 50 ft in a pistol standard event [10], 14% in the British Columbia, 48 shot firearms course of fire [11], or 1%–3% when shooters used a 9.0 mm calibre or an air pistol at 10 m [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…2 Urgentnost situacija na terenu često zahtijeva da policijski službenik u vrlo kratkom vremenu izvrši analizu aktuelnih informacija, donese pravovremene i ispravne odluke, koje moraju biti u skladu sa zakonom, i realizuje ih na najbolji način. 3 U situacijama kada dođe do upotrebe sredstava sile, bilo da policijski službenik treba da odbije napad od sebe ili drugog lica ili izvrši službenu radnju, do izražaja dolaze elementi borilačkih vještina koji su stečeni prije nego što se desio napad 4 . Samo pod uslovom da se uvježbavanje i usavršavanje vrši konstantno, sav trud i rad uložen za sticanje vještina kvalitetno je utrošeno vrijeme i povećava šanse za uspješno rješavanje problemske situacije s minimumom štetnih posljedica po građane i po policijske službenike.…”
Section: Uvodunclassified